Considerations regarding the constitutional obligation determining the financing source for budgetary expenditures - Florentina Camelia Stoica (Juridical Tribune, 2016)
This study examines the relation between constitutionality and opportunity in order to adopt regulations in matters of economy and finance. The analysis concerns in particular the regulation process on budgetary expenditures, respectively the constitutional obligation to indicate the source of financing for these expenses. The legal and jurisprudential landmarks identified are likely to reveal the delicate issues of balancing the concurring interests, as well as the constitutionalisation tendency of certain obligations imposed by the law of public finances and, respectively, the Fiscal Responsibility Law in the sense of transforming them into “constitutional criteria” through the application of Article 138 (5) of the Constitution.